Mental Health and Psychosocial Needs of Patients Being Treated for Opioid Use Disorder in a Primary Care Residency Clinic - Stephanie A. Hooker; Michelle D. Sherman; Mary Lonergan-Cullum; Adam Sattler; Bruce S. Liese; Kathryn Justesen; Tanner Nissly; Robert Levy (Journal of Primary Care & Community Health, 2020)
Purpose: Primary care is an ideal setting to deliver efficacious treatments for opioid use disorder (OUD). Primary care providers need to be aware of other concerns patients with OUD might have in order to provide comprehensive care. This study describes the prevalence of mental health, comorbid substance use, and psychosocial concerns of patients seeking treatment for OUD in primary care and their relation to 6-month treatment retention. Methods: Patients (N = 100; M age = 34.9 years (SD = 10.8), 74% white, 46% female) with OUD who were starting treatment with buprenorphine at an academic family medicine residency clinic completed surveys of mental health concerns (depression, anxiety, trauma), psychosocial needs (food insecurity, income, transportation, employment), and demographic variables. Chart reviews were conducted to gather information on comorbid substance use, mental health diagnoses, and 6-month treatment retention. Results: Mental health symptoms were highly prevalent in this sample (44% screened positive for anxiety, 31% for depression, and 52% for posttraumatic stress disorder). Three-quarters reported use of illicit substances other than opioids. Many patients also had significant psychosocial concerns, including unemployment (54%), low income (75%), food insecurity (51%), and lacking reliable transportation (64%). Two-thirds (67%) of the sample were retained at 6 months; patients who previously used intravenous opioids were more likely to discontinue treatment ( P = .003). Conclusions: Many patients receiving treatment for OUD have significant mental health problems, comorbid substance use, and psychosocial concerns; interestingly, none of these factors predicted treatment retention at 6 months. Primary care clinics would benefit from having appropriate resources, interventions, and referrals for these comorbid issues in order to enhance overall patient well-being and promote recovery.